Factors Influencing Job Satisfaction of Personal Assistants in Universiti Malaysia Sabah / Tracy Olovia R Liberatus - Liberatus, Tracy Olovia R (2012)
The study was conducted to identify factors influencing job satisfaction among the Personal Assistants in Universiti Malaysia Sabah. Job satisfaction Survey (JSS) questionnaire containing nine facets of job satisfaction was used for data collection from all the Personal Assistants in Universiti Malaysia Sabah. It aimed to identify the positive association between overall job satisfaction and facets of job satisfaction among Personal Assistants in Universiti Malaysia Sabah and also to identify the relationship between demographic factors (marital status) with job satisfaction among Personal Assistants in Universiti Malaysia Sabah. Findings showed that there are dissatisfied in the facets of job satisfaction: promotion and contingent rewards. This study used Pearson Correlation test and crosstabulations test.